Proceedings of the 15th International Academic MindTrek Conference: Envisioning Future Media Environments 2011
DOI: 10.1145/2181037.2181067
|View full text |Cite
|
Sign up to set email alerts
|

Understanding user behavior in a local social media platform by social network analysis

Abstract: Characterizing user behavior by social network analysis in social media has been an active research domain for a long time. However, much previous research has focused on the large-scale global social media such as Facebook, Wikipedia and Twitter. Comparatively, little research has been done for the local social media. In this paper, We study the user behavior by social network analysis in a campus-based social media platform for exchanging goods and services. We also study the correlation between social netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The use of NodeXL was also recently highlighted in a study which identified polarised crowds and opinion leaders in topics related to a viral hashtag on Twitter around abortion titled “#ShoutYourAbortion” (Ahmed, 2018). NodeXL in academic work has also ranged from the analysis of blackboard discussion boards (Waters and Gasson, 2012), blogs (Saffer, 2013), personal e-mail networks (Bengfort and Xirogiannopoulos, 2015), internal security (Gamachchi et al , 2017), medical data analysis (Piepoli et al , 2012), political sponsorship (Piepoli et al , 2012), news stories (Quinn and Powers, 2016), campus-based social media platforms (Tang et al , 2011) and Wikipedia (Ferron and Massa, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The use of NodeXL was also recently highlighted in a study which identified polarised crowds and opinion leaders in topics related to a viral hashtag on Twitter around abortion titled “#ShoutYourAbortion” (Ahmed, 2018). NodeXL in academic work has also ranged from the analysis of blackboard discussion boards (Waters and Gasson, 2012), blogs (Saffer, 2013), personal e-mail networks (Bengfort and Xirogiannopoulos, 2015), internal security (Gamachchi et al , 2017), medical data analysis (Piepoli et al , 2012), political sponsorship (Piepoli et al , 2012), news stories (Quinn and Powers, 2016), campus-based social media platforms (Tang et al , 2011) and Wikipedia (Ferron and Massa, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Lo et al [48] conducted a study on Hong Kong visitors which revealed that over 89% of visitors take photos; however, only 41% are willing to post them online, with results indicating that those who posted opted to post the photos on social media sites. Furthermore, Tang et al [49] analyzed user behaviors by applying social network research to a university campus-based social media site on which personal items and resources are exchanged, with findings indicating that user experiences remained highly positive. When applying social network analysis, however, Tang et al [49] suggested using Facebook or Twitter as platforms for analysis.…”
Section: Collaboration Knowledge and Information-sharingmentioning
confidence: 99%
“…Furthermore, Tang et al [49] analyzed user behaviors by applying social network research to a university campus-based social media site on which personal items and resources are exchanged, with findings indicating that user experiences remained highly positive. When applying social network analysis, however, Tang et al [49] suggested using Facebook or Twitter as platforms for analysis. Rathonyi [50] explored visitor motivation to share information, with survey findings reporting that both the bulk of students using social networking websites daily and students who did not use the same channels for planning a trip preferred to ask fellow students, friends, and relatives for recommendations.…”
Section: Collaboration Knowledge and Information-sharingmentioning
confidence: 99%
“…Social networks according to [16] are an avenue through which users are able to share data and information that can be in the form of audio, video, picture or text. Users connect with each other by forming edges, which allow information to be transferred.…”
Section: A Social Networkmentioning
confidence: 99%